Bifidobacterium longum JBLC-141 alleviates hypobaric hypoxia-induced intestinal barrier damage by attenuating inflammatory responses and oxidative stress - Li, Xiang-Yang; Shang, Jin; Wang, Xiao-Juan; Ma, Hui-Ping; Ren, Long-Fei; Zhang, Lei (Frontiers in Microbiology, 2024)
Hypobaric hypoxia exposure occurs at high altitudes, including plateaus, and affects normal intestinal function and microbiota composition. Exposure induces an intestinal inflammatory response and oxidative stress injury, ultimately disrupting intestinal homeostasis and causing barrier damage. Thus, due to its anti-inflammatory, antioxidative, and intestinal microbiota-regulating properties, Bifidobacterium longum is a potentially effective probiotic intervention to protect the intestinal barrier during low-pressure hypoxia on plateaus. However, its mechanism of action is not fully defined. In this study, we investigate the mechanism by which B. longum intervenes in intestinal barrier damage caused by plateau low-pressure hypoxia. To this end, an in vivo model is established by exposing rats to a simulated low-pressure hypoxic plateau environment. The experimental rats were subsequently supplemented with a B. longum strain (JBLC-141) extracted from the feces of healthy adults in Bama, Guangxi. B. longum JBLC-141 mitigates the effects of plateau low-pressure hypoxia on the rat intestinal barrier. This is achieved by activating the intestinal Kelch-like ECH-associated protein 1 (KEAP1)/nuclear factor erythroid 2-related factor 2 (NRF2) pathway, alleviating plateau hypoxia-induced intestinal oxidative stress injury. B. longum JBLC-141 also attenuates the inflammatory response and upregulates the expression of the tight junction proteins claudin-1, occludin, and zonula occludens-1. Furthermore, it reduces intestinal permeability, effectively ameliorating and repairing the barrier histological damage induced by the plateau low-pressure hypoxic environment. In addition, B. longum JBLC-141 positively regulates the intestinal microbiota, increasing the relative abundance of beneficial bacteria while reducing that of pathogenic bacteria and maintaining intestinal flora homeostasis in rats.